Effects of bargaining legislation on worker and management reconciliation decisions—a bivariate duration analysis - Reza, Sadat (2024)
We examine bargaining legislation effects on the union and management reconciliation decisions following announcement of a strike using a bivariate duration model. The durations associated with the two groups are latent, and we argue that under weak assumptions the key parameters are identified. Simulation studies show that the latent parameters are reliably estimable in finite samples. We use a large Canadian dataset to estimate effects of several policies on the strike continuation probabilities of workers and management. Our results suggest that several of these policies affect workers’ decision to continue stoppage or not. On the other hand, management reconciliation decision is largely unaffected by most of these policies. Our study also reveals interesting behavioural differences among management and workers depending on jurisdiction, sector, and firm characteristics.